1996
DOI: 10.1210/endo.137.11.8895364
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha: a multifunctional regulator of mammary gland development.

Abstract: To determine whether tumor necrosis factor-alpha (TNF alpha) plays a physiological role in normal mammary gland development, TNF alpha and TNF receptor expression were measured in epithelial cells (MEC) isolated from mammary glands of virgin, pregnant, lactating, and postlactational (day 7 of involution) rats. TNF alpha messenger RNA (mRNA) increased significantly during pregnancy, then decreased during lactation and involution. The 26-kDa transmembrane form of TNF alpha protein, undetectable in MEC from virgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Consistent with the constitutive mRNAexpression of proinflammatory cytokines in mammary tissues [60], the proinflammatory cytokine production here was also seen in mammary tissues obtained from sows before inoculation with E. coli. These findings are consistent with previous studies in rats, humans as well as in cows where some baseline constitutive production of cytokines takes place in normal mammary glands [7,23,56]. Similarly, proinflammatory cytokines have also been found in serum/plasma collected from healthy pregnant sows [59] as well as pregnant women [4,24,57].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the constitutive mRNAexpression of proinflammatory cytokines in mammary tissues [60], the proinflammatory cytokine production here was also seen in mammary tissues obtained from sows before inoculation with E. coli. These findings are consistent with previous studies in rats, humans as well as in cows where some baseline constitutive production of cytokines takes place in normal mammary glands [7,23,56]. Similarly, proinflammatory cytokines have also been found in serum/plasma collected from healthy pregnant sows [59] as well as pregnant women [4,24,57].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings 8 , analysis of HeLa-vector cells showed that IKKβ and IKKγ are detectable in a prominent pool with a relative molecular mass (M r ) of 700,000 (fractions [10][11][12] and also in a pool of ~300 K (fractions 14 and 15; Fig. 3a).…”
supporting
confidence: 91%
“…4b). Previous work has demonstrated that the effects of TNFα on mammary epithelial cells are of physiological importance for mammary gland morphogenesis during puberty and pregnancy [11][12][13][14][15] . To determine whether these effects of TNFα are regulated by MUC1, primary mouse mammary epithelial cells (MMECs) were transfected with control or mouse-specific Muc1 siRNAs (Fig.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Real-time quantitative reverse transcriptase polymerase chain reaction assay for interleukin-13, interferon-c, tumour necrosis factor-a and transforming growth factor-b 1 messenger ribonucleic acid Total lung ribonucleic acid was extracted from frozen lungs using a commercial kit (ISOGEN, Nippon Gene Co., Toyama, Japan) according to the standard procedure [11]. A two-step reverse transcriptase polymerase chain reaction (RT-PCR) procedure was used according to the protocol of the TaqMan Gold RT-PCR Kit (Perkin-Elmer Applied Biosystems, Foster City, CA, USA).…”
Section: Bronchoalveolar Lavage and Cell Countingmentioning
confidence: 99%